PEMBELAJARAN DAN PENERAPAN PHBS DI SEKOLAH MELALUI MEDIA LAGU DOLANAN JAWA - Sari, Dian Lukita; Pangesti, Tri Puji; Susanta, Dedi; Haryanti, Titik; Ahya, Rahmatul (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
The school as one of the targets for PHBS institutions that need to get attention given school age (ages 6-10) is vulnerable to the emergence of a variety of ailments. According to the WHO (2007) States that every child is 100,000 years Indonesia died due to diarrhea, kecacingan incident Number 40-60% (Ministry of health, 2005) and 23.2% of school children anemia (YKB, 2007). The goal of this program is to increase the degree of health and knowledge of PHBS, availability of support facilities and the implementation of indicators 8 PHBS behavior at school. Implementation of the PHBS preparation methods, learning, application and final event. The result of the program, the target public is able to develop the PHBS in school with the establishment and inauguration of the Health Ambassadors OS3 9.